2021
DOI: 10.1186/s13765-020-00570-6
|View full text |Cite
|
Sign up to set email alerts
|

Irigenin exerts anticancer effects on human liver cancer cells via induction of mitochondrial apoptosis and cell cycle arrest

Abstract: Irigenin has been reported to exhibit remarkable anticancer effects against several human cancers. Nonetheless, the anticancer effects of irigenin against the human liver cancer cells are still largely unexplored. Consistently, this study was designed to evaluate the anticancer effects of irigenin against human liver cancer cells and to unveil the underlying molecular mechanisms. The results showed that irigenin significantly (p < 0.05) inhibited the growth of the human HepG2 and SNU-182 liver cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For example, irigenin has been proved to inhibit the development of human colon cancer by suppressing of ERK/MAPK signal pathway (Zhan et al, 2021). Similar anticancer effects focused on apoptosis in the most of these studies (Xu et al, 2018;Xu et al, 2021). However, the function of irigenin in GBM remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, irigenin has been proved to inhibit the development of human colon cancer by suppressing of ERK/MAPK signal pathway (Zhan et al, 2021). Similar anticancer effects focused on apoptosis in the most of these studies (Xu et al, 2018;Xu et al, 2021). However, the function of irigenin in GBM remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Isoflavone compounds, including irigenin, are important medicinal ingredients in this plant ( Ito et al, 2001 ). Current studies have revealed that irigenin not only shows the effects of antioxidative and anti-inflammatory, but also has anti-tumor activity ( Woźniak and Matkowski, 2015 ; Guo et al, 2020 ) including inhibition of cancer cell metastasis ( Amin et al, 2016 ), promotion of cell apoptosis ( Xu et al, 2018 ), cell cycle arrest ( Xu et al, 2021 ), autophagy ( Zhan et al, 2021 ) and extracellular matrix degradation ( Zhang et al, 2021 ). These antitumor effects of irigenin are associated with the modulation of various signaling pathways.…”
Section: Introductionmentioning
confidence: 99%